First record of the tarantula genus Bumba (Araneae: Theraphosidae) from Bolivia, with the description of a new species - Ferretti,Nelson E. (2021)
ABSTRACT A new species of Bumba Pérez-Miles, Bonaldo & Miglio, 2014 is described and illustrated. This species comprises the first record of the genus for Bolivia. Bumba paunaka sp. nov. differs from the other species in the genus in the black longitudinal band on abdomen, in the long and slender embolus of the palpal bulb and in the thin and long subapical spine of the retrolateral branch of tibial apophysis. Females additionally differ in the spermathecal morphology. Finally, a distribution map for all known species of Bumba is presented.